The Relationship between Sanitary Hygiene and Coliform Bacteria Contamination at Refill Drinking Water Depots - Heni Fa’riatul Aeni; Iin Kristanti; Yani Rohayani; Lilis Banowati (EDUPEDIA Publisher, 2023)
Objective: This study aims to determine the relationship between sanitation hygiene and Coliform bacteria contamination in refilled drinking water in Waled District in 2023. Methods: This study uses an analytic observational design with a cross-sectional approach where the researcher will simultaneously observe or measure the independent and dependent variables (period). The sampling technique is total sampling with a sample of 30 refilled drinking water depots with 30 workers—data collection through observation and interviews. Data analysis was used, namely data analysis using Fisher's exact test. Results: Based on laboratory tests, it was found that more than half of the refilled drinking water depots were contaminated with coliform bacteria as much as 60%. After analysis, it was found that factors related to Coliform bacteria contamination in filled drinking water were access to sanitation facilities (p = 0.001), and worker behavior (p = 0.001), while factors that were not related were drinking water treatment facilities (p = 0.063), raw water (p = 1.000) and consumer service hygiene (p = 0.418). Conclusion: Of the five sanitation hygiene factors, those that have a significant relationship with coliform bacteria contaminants are sanitation facilities and behavior, while drinking water treatment facilities, raw water, and consumer service hygiene are factors that are not significant in determining bacterial contamination.